Existing protected areas provide a poor safety‐net for threatened Amazonian fish species. Issue 5 (15th September 2020) - Dagosta, Fernando C. P.; de Pinna, Mário; Peres, Carlos A.; Tagliacollo, Victor A.
Abstract: Freshwater ecosystems represent less than 0.01% of Earth's surface water but proportionately encompass the most species‐rich environment on the planet, including nearly one‐third of all vertebrate species. Even though inland continental waters are widely regarded as highly endangered ecosystems, their species assemblages are mostly ignored in conservation plans, largely because spatial patterns of freshwater species remain poorly understood. This is particularly severe throughout the Neotropics, most notably in the Amazon superbasin, where the sheer biotic diversity is coupled with a severe lack of biodiversity knowledge at several levels. Spatial patterns of Neotropical freshwater fishes focusing mainly on the Amazon superbasin were investigated. First, Endemic Amazonian Fish Areas (EAFAs) representing central units for the conservation of continental fishes were delimited. Interpolated maps were then analysed using alternative methodologies to delimit spatial patterns of diversity and endemicity across the Amazon superbasin. Several biogeographical analyses used a comprehensive dataset of species and geographical coordinates of Amazonian fishes. The results reveal well‐defined spatial patterns of species richness and endemicity in the Amazonian fish fauna, showing that most protected areas are concentrated in a single bioregion (Amazon lowlands). Those areas are incongruent and insufficient to protect endemic and threatened species, which are mostly distributed in upland regions. Effective conservation of the Amazonian fish fauna should include EAFAs within protected areas, especially those undergoing deforestation and hydropower development pressure and containing a high concentration of threatened species. The following EAFAs should be considered as conservation priorities: Upper Araguaia, Upper Tocantins, Lower Teles Pires/Serra do Cachimbo, Chapada dos Parecis and Upper Marañon. These regions should be urgently protected to avert the loss of important trophic relationships and unique elements of the Amazonian fish fauna.